WALL-JET ELECTRODE LINEAR SWEEP VOLTAMMETRY - Compton, R; Fisher, A; Latham, M; Brett, C; Brett, A (1992)
Theory is presented which predicts the linear sweep voltammetry behavior at the wall-jet electrode for a reversible couple. The scan rate and electrode geometry dependences are established, and hence the requirements for the measurement of true "steady state" hydrodynamic voltammograms are defined. Theory is found to be in good agreement with experiments conducted on the oxidation of the ferrocyanide anion in aqueous solution. © 1992 American Chemical Society.